Effect of regulated deficit irrigation on the content of soluble sugars, organic acids and endogenous hormones in Cabernet Sauvignon in the Ningxia region of China. (15th May 2020) - Yang, Bohan; Yao, Heng; Zhang, JunXiang; Li, Yueqi; Ju, Yanlun; Zhao, Xianfang; Sun, Xiangyu; Fang, Yulin
Graphical abstract: Highlights: The glucose and fructose contents were increased by the RDI treatments. Most genes associated with sugar unloading were up-regulated by RDI. The tartaric acid, malic acid and citric acid contents were decreased by RDI. ABA increased from E-L 33–38, and IAA, GA3, JA-Me and BR decreased from E-L 33–34. Abstract: The aim of this work, which was conducted in 2017 and 2018, was to gain insight into the effects of regulated deficit irrigation (RDI) treatments on the content of soluble sugars, organic acids and endogenous hormones in Cabernet Sauvignon. The RDI treatments slightly decreased the hundred-grain weight and total acid content before vintage but significantly increased the soluble solids content, juice pH and reducing sugar content. The glucose and fructose contents were increased by the RDI treatments, and the ratio of G:F was reduced. Most genes associated with sugar unloading were upregulated by RDI, especially in the RDI1 group. The tartaric acid, malic acid and citric acid contents were decreased by RDI. Under the RDI treatments, the ABA content increased from E-L 33 to 38, and the IAA, GA3, JA-Me and BR contents decreased from E-L 33 to 34. The results of this study ultimately benefit the promotion of RDI measures, and our data might be useful for the improvement of wine grape quality.